Molecular Analysis of phe Operon Genes determining Phenol-Degrading Pseudomonas sp. from Polluted Sites in Baghdad City: Molecular Analysis of phe Operon Genes - Tawfeeq, Huda Rasheed; Al-Jubori, Sawsan Sajid; Mussa, Amel Hussaein (Proceedings of the Pakistan Academy of Sciences: B. Life and Environmental Sciences, 2022)
: Phenolic compounds are toxic to plants, animals and even for microorganisms at low concentrations. Because of this toxicity, it is important that soils polluted with these compounds to be remediated immediately. Pseudomonas aeruginosa and Pseudomonas putida, as well as their both intra- and extradiol enzymes, were the targets of this study, which aimed to detect the enzymes responsible for phenol degradation capability in bacteria and the genetic variation of the catabolic genes related to the phe operon among the positive isolates. In this study one hundred twenty five samples of contaminated soils have been collected from different sources at Baghdad city (89 samples from Daura refinery, 21 samples from private electricity generators and 15 samples from different farm lands). Collected samples have cultured on mineral salt medium as well as using differential and selective media, then diagnosed by classical biochemical tests and VITEK system beside using Housekeeping gene 16s rDNA for molecular diagnosis. The results of VITEK system revealed that 29 /89 (32.5 %) of samples from Daura refinery had P. aeroginosa isolates and only one sample 1/89 (1.1 %) of P. putida. On the other hand, none of the samples from generators (0 %) were P. aeroginosa and 5/21(23.8 %) were P. putida while 5/15 (33.3 %) samples of farm lands were P. aeroginosa and (0 %) were P. putida. Molecular diagnosis using 16S rDNA detected 40/125 (32 %) positive isolates for Pseudomonas sp.; 34 (85 %) isolates for P. aeruginosa and 6 (15 %) isolates for P. putida. Phenol degradation capability of the forty isolates has been tested on mineral salt medium using different concentrations of phenol (100 ppm to 1500 ppm) and all of them (100 %) were able to degrade phenol to 600 ppm but a number of 4 isolates (10 %) have exceeded this concentration to 1200 ppm and only one isolate (2.5 %) tolerated phenol to the maximum level which is 1500 ppm. Phenol degrading isolates were subjected to PCR technique to detect the phe-like genes: catechol 1, 2 dioxygenase (cat1), and catechol 2, 3 dioxygenase (cat2). As a result, this set of enzymes were found in the whole five (12.5 %) isolates that effectively degraded phenol to the concentration of 1200 ppm and 1500 ppm.